Investigation of Melaleuca leucadendron L. from South Sumatra: Phytochemicals and IC50-Based Antioxidant Potential - Ernia, Rima; Sitindaon, Rina SE; Antara, Nyoman Yudi (Universitas Negeri Medan, 2025)
Melaleuca leucadendron L. (commonly known as Gelam wood) is a plant that thrives in the swampy regions of South Sumatra. The utilization of this plant has historically been limited to its wood, leaving the potential of its leaves and seeds largely unexplored. Therefore, this study aimed to identify the species of Gelam wood and investigate the phytochemical content and antioxidant potential of its leaves and seeds.The methodology involved methanol extraction of the plant material, followed by comprehensive phytochemical screening and an antioxidant activity assay using the DPPH method.The phytochemical analysis confirmed the presence of several key compounds, with the Gelam extracts testing positive for Alkaloids, Flavonoids, Steroids, Saponins, Tannins, and Triterpenoids. Furthermore, the extract from the leaves and seeds demonstrated potent antioxidant activity, evidenced by an IC50​ value of 47.56 ppm, which classifies it as a strong antioxidant (<50 ppm).This research highlights the significant therapeutic potential of Melaleuca leucadendron leaves and seeds, suggesting they are valuable sources of natural antioxidants